2020
DOI: 10.1142/s0217979220401633
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on determining the vertical tyre force of a tractor semi-trailer

Abstract: The vertical tyre force is crucial to the study of the dynamics of a tractor semi-trailer. The paper presents an experimental method for determining the vertical tyre force by determining the vertical acceleration of the un-sprung mass and the vertical acceleration of the sprung mass when the tractor semi-trailer moves. The results of this study form the basis for determining the dynamic tyre force without the installing of sensors on road.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Matlab-Simulink software was used to investigate and compare the longitudinal friction coefficient function of the wheel according to the longitudinal slide coefficient ( ) determined by experiment and the function ( ) simulated according to Ammon tire model on the same type of road with the maximum longitudinal friction coefficient xmax=0.89 and the minimum longitudinal friction coefficient xmin=0.72 [4,5] The system of dynamic equations of the tractor semitrailer are as follows [5]: 12 and 13. The survey results showed that when the input function ( ) determined by experiment and Ammon function were used, the average error of force Fx was 11,81% and the average error of force Fz is 19 and 25%.…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Matlab-Simulink software was used to investigate and compare the longitudinal friction coefficient function of the wheel according to the longitudinal slide coefficient ( ) determined by experiment and the function ( ) simulated according to Ammon tire model on the same type of road with the maximum longitudinal friction coefficient xmax=0.89 and the minimum longitudinal friction coefficient xmin=0.72 [4,5] The system of dynamic equations of the tractor semitrailer are as follows [5]: 12 and 13. The survey results showed that when the input function ( ) determined by experiment and Ammon function were used, the average error of force Fx was 11,81% and the average error of force Fz is 19 and 25%.…”
Section: Simulationmentioning
confidence: 99%
“…Thus, in order to determine the longitudinal friction coefficient function x(t), Fx(t) and Fz(t) should be known [4]. *Corresponding Author Institutional Email: tungnt@vlute.edu.vn (N. Thanh Tung)…”
Section: Introductionmentioning
confidence: 99%
“…The vertical tyre force is crucial to the study of the dynamics of a tractor semi-trailer. Tung, Huong and Kiet present in their paper [2] an experimental method for determining the vertical tyre force by determining the vertical acceleration of the un-sprung mass and the vertical acceleration of the sprung mass when the tractor semi-trailer moves. The results of this study form the basis for determining the dynamic tyre force without installing of sensors on road [2].…”
Section: Introductionmentioning
confidence: 99%